2016
DOI: 10.1007/s10961-016-9504-5
|View full text |Cite
|
Sign up to set email alerts
|

Total factor productivity and the role of entrepreneurship

Abstract: The absence of evidence in the scholarly literature for a tested long-term relationship between entrepreneurship and economic growth is at odds with the importance attributed to entrepreneurship in the policy arena. The present paper addresses this absence, introducing entrepreneurship using four different and accepted models explaining the total factor productivity of twenty OECD countries with data for the period 1969-2010. Traditionally, entrepreneurship is not addressed in these models. We show that in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 111 publications
4
68
0
2
Order By: Relevance
“…If we have difficulty defining entrepreneurship as an individual or firmlevel phenomenon, what hope do we have of deciding what 'entrepreneurship' means as a county-level phenomenon?" Researchers at the country-level use measures of self-employment, new firm startups or the Global Entrepreneurship Monitor defined Total Entrepreneurship Activity (TEA) rate (Carree and Thurik 2003;Erken et al 2016). In contrast, we propose that country-level entrepreneurship should be treated as a systemic phenomenon similar to the way the literature on National Systems of Innovation (NSI) treats country-level innovation, institutions and policies.…”
Section: Introductionmentioning
confidence: 99%
“…If we have difficulty defining entrepreneurship as an individual or firmlevel phenomenon, what hope do we have of deciding what 'entrepreneurship' means as a county-level phenomenon?" Researchers at the country-level use measures of self-employment, new firm startups or the Global Entrepreneurship Monitor defined Total Entrepreneurship Activity (TEA) rate (Carree and Thurik 2003;Erken et al 2016). In contrast, we propose that country-level entrepreneurship should be treated as a systemic phenomenon similar to the way the literature on National Systems of Innovation (NSI) treats country-level innovation, institutions and policies.…”
Section: Introductionmentioning
confidence: 99%
“…The popularity of the concept originates from economics where entrepreneurship is accepted as one key process to economic growth and development and the entrepreneur as the economic agent in that process (Cantillon, 1775;Say, 1816;Schumpeter, 1934). Nitu-Antonie et al (2017), Lee and Xin (2015), Chen, (2014), Erken et al (2014), Salman and Badr (2011), Vazquez et al (2010) and Audrestch (2007) are among those who found that entrepreneurship is an important factor for economic growth, while Kardos (2012), Stefanescu and On (2012) and Talmaciu (2012) found correlations between entrepreneurship activities and economic development. Decker et al (2014), Haltiwanger et al (2013) and Audretsch and Fritsch (2003) are among the various researchers who found that entrepreneurship creates jobs in an economy.…”
Section: The Concept Of Entrepreneurshipmentioning
confidence: 99%
“…However, exploiting business opportunities does not always increase overall productivity (Baumol, 1990). One study suggests that the productivity effect of business ownership is positive (Erken, Donselaar and Thurik, 2016). However, another study finds the economic growth effects (and hence most likely the productivity effects) to be negative in developing countries.…”
Section: Immigration and Entrepreneurshipmentioning
confidence: 99%